Assessment of the Nurse’s Role Regarding drug Administration of Cardiovascular Patients - Younis, Yousif; hussien, Ronak (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: The aim of the study was, to assess the nurse’s role regarding cardiovascular drug administration in Erbil city. Methodology: A descriptive survey was conducted in Hawler teaching and Rizgari teaching Hospitals. The number of samples is 50 nurses; the period of the study was started from 15th of November 2008 up to the end of March 2009. A questionnaire was developed by investigators based on extensive review of available studies and literatures. Data were collected through application of observational check list consist of two part, part one was demographic sheet and part two about nurse’s responsibility regarding medication administration which include (before, during, after drug administration). Data were analyzed through the application of descriptive statistical analysis such as (frequency, percentages and grand mean of scores). Results: Results showed that (72%) of nurses were within age group of (31-40) years, (66%) of them were married, and (64%) of them were institute graduated. The study showed that nurses’ practices were inadequate with low grand mean of score in most items regarding assessment of patients before, during and after drug administration. Recommendations: Increase nursing staff awareness about cardio vascular drug administration through performs training on cardiac medication administration, follow up nurses’ practice during drug administration and follow up the five rights of cardiac drug administration.